PEMBELAJARAN GERAK LARI SAMBIL MENGUCAPKAN KATA DASAR UNTUK SISWA SDLB TUNARUNGU DI SLB NEGERI SEMARANG TAHUN 2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
Purpse of this study is to determine whether the motion of running while learning to say the word can be doneby elementary students in the deaf SDLB SLB Semarang Year 2013 . This study uses research development .The procedure includes product development needs analysis , develop initial product , expert validation andrevision , testing and revision of small groups , large groups and test the final product . From the test resultsobtained by experts the average percentage of product analysis results of 92 485 % . It can therefore be used totest small groups . The results of the student questionnaire data on a small test group gained an average of90.83 % with a percentage response . And questionnaire data from a large group of students obtained testanswers with a percentage of 91.66 % . The data was collected using field observations and questionnaires wereobtained from expert evaluation and the results of the questionnaire by the students . The data analysistechnique used is descriptive percentage . Based on the research data , it was concluded that the motion learningrun by the utterance variations of basic words effectively and in accordance with the needs of the students sothat they can be used in learning Penjasorkes .